Dengue Fever Management Strategy Through the Tunggal Dara Program - Bagaskara, Imanuel; Zulfiningrum, Rahmawati (CV. Rayyan Dwi Bharata, 2024)
The phenomenon of Dengue Fever is currently increasing in the Semarang City Area, this has caused the Semarang City Government to create a program to overcome Dengue Fever which makes it easier for the community and health units to suppress cases of Dengue Fever. The aim of this research is to determine the Communication Strategy of the Tunggal Dara Program in Tlogosari Kulon Village, Semarang. This research uses the theory of communication strategy stages which consists of: analysis and planning, design and implementation of plans, implementation of strategies, follow-up and commitment, and tracking of results. This research uses a qualitative descriptive approach with data collection methods through in-depth interviews and observation. The research results show that the stages of the communication strategy in the Tunggal Dara program are as follows: 1) Cadres carry out analysis by directly monitoring hygiene activities in the community and planning for the success of the Tunggal Dara program is carried out in collaboration between government sectors to tackle dengue fever; 2) Design socialization to support the Tunggal Dara program through pamphlets, applications and websites as well as various posts on social media, as well as communication between cadres and community leaders for the smooth running of the Tunggal Dara program in the community; 3) Implementation of strategies using persuasive communication techniques with outreach regarding the Tunggal Dara Program to break the chain of dengue fever. 4) The Tunggal Dara Program requires increased outreach and direct visits to the community as well as increased complaint services both offline and online, as well as additional administration of pesticides to reduce the growth of larvae. mosquito; 5) Tracking of results is obtained through recapitulation of PJN reports which are routinely reported by the public every week. The success of the Tunggal Dara program can be seen from the decrease in the number of dengue fever sufferers who can be accessed through the Tunggal Dara Program application or website. This program still needs improvements such as outreach to the community, cadre training and improving complaint services, administering pesticide drugs in the community so that the program becomes better.